LAPORAN KASUS ABORTUS IMINENS JUNI 2015 FAKTOR RESIKO, PATOGENESIS, DAN PENATALAKSANAAN - Kiki Sanjaya Dharma (Intisari Sains Medis, 2015)
Introduction: One of the most complications in pregnancy it was a bleeding , that could happen to any the gestational age .Young in pregnancy , often connected with abortus , miscarriage , and loss of early pregnancy .Abortus is defined as the threat or spending the products of conception before a fetus can live outside the utery. Constitutes gestational age is less than 20 weeks or fetus weight less than 500 grams .Abortus imminens is pervaginam bleeding in pregnancy before 20 weeks without accompanied the release of the products of conception and dilatation of the uterus.Cases: Female patient , 31 years , the balinese ethnic coming to the emergency room the hospital with complaints pervaginam bleeding. Said to be initially were bleeding spots that its color red .Then there are black coloured bloodlump, there is no tissue.